1999
DOI: 10.1006/ofte.1998.0292
|View full text |Cite
|
Sign up to set email alerts
|

Large Mode Area Fibers for High Power Applications

Abstract: We review our recent work toward designing large mode area fibers for high power applications. We show that appropriately designed doped multimode fibers can be used to provide robust single-mode output when used in Ž . fiber laser cavities. Single-mode SM fiber mode field diameters of ; 35 m are demonstrated with record SM pulse energies of 0.5 mJ at 1550 nm with a repetition rate of 200 Hz. Energies approaching 1 mJ are obtained with a slight compromise in mode quality. A modification in the laser cavity res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(57 citation statements)
references
References 10 publications
0
57
0
Order By: Relevance
“…We have recently reported a Q-switched fiber laser capable of generating 2.3-mJ pulses in a cladding-pumped configuration [3] based on LMA fiber. The core area, in this case, was 1300 m , more than a factor of 50 greater than that in standard Yb-doped single-mode fibers [5]. We have also reported CW laser operation of multimode fibers with a tapered section for suppression of higher order modes [6].…”
Section: Introductionmentioning
confidence: 70%
“…We have recently reported a Q-switched fiber laser capable of generating 2.3-mJ pulses in a cladding-pumped configuration [3] based on LMA fiber. The core area, in this case, was 1300 m , more than a factor of 50 greater than that in standard Yb-doped single-mode fibers [5]. We have also reported CW laser operation of multimode fibers with a tapered section for suppression of higher order modes [6].…”
Section: Introductionmentioning
confidence: 70%
“…Furthermore, both Nd 3+ and Yb 3+ emit in the wavelength range of ∼ 1 µm, and thus the output power from claddingpumped Nd 3+ -Yb 3+ codoped fiber lasers (NYDFL) can be scaled to hundreds of watts [6], [7]. In order to achieve such high output powers without reaching the threshold of nonlinear effects, the dimensions of the fiber core must be increased and the fiber becomes intrinsically multimode [8]. Bending losses can be applied to discriminate the fundamental LP 01 mode from higher order modes so that the laser output becomes practically single mode [9].…”
Section: +mentioning
confidence: 99%
“…We note that the Nd 3+ transitions 4 F 3/2 -4 I 13/2 at ∼ 1300 nm can also contribute to the ASE power, but we found that this contribution is small for the range of parameters assumed in this work, and therefore, it was neglected. The rate of change of the ASE spectral power densities and the pump power along the fiber length are given below by (8) and (9). Here, dP…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The key technology in this progress is the development of larger mode field area fibers (especially very large mode field area (VLMA) fibers with mode-field diameters (MFDs) beyond 50 µm) which is an effective way to increase the storage energy and mitigate intensity-related nonlinear effects [3] .…”
Section: Introductionmentioning
confidence: 99%